Testing The Fe Content of Green Spinach Leaf Extract Using the AAS Spectrophotometry Method - Prasasti, Azmi; Sari Prayudeni; Abi Mas Udianto; Stephanie Devi Artemesia; Anung Kustriyani; Elsa sarif (Journal of Tropical Chemistry Research and Education, 2026)
Green spinach (Amaranthus hybridus L.) is a plant that contains vitamin K, vitamin C, vitamin E, vitamin A, and vitamin B complex. Green spinach is rich in iron to prevent anemia. Iron plays an important role in the manufacture of hemoglobin, a protein in blood cells, regular consumption of green spinach can increase hemoglobin levels. The purpose of this study was to determine the level of Fe in an extract of spinach leaves with the maceration method of aquadest solvent. Measurement of Fe levels using AAS Spectrophotometry (Atomic Absorption Spectrophotometry). The results of the study obtained the Fe content of thick spinach leaf extract of 0.0190%.